Additive value of the CRUSADE score to the GRACE score for mortality risk prediction in patients with acute coronary syndromes. (15th October 2017) - Cordero, Alberto; Rodriguez-Manero, Moisés; García-Acuña, Jose M.; López-Palop, Ramón; Cid, Belen; Carrillo, Pilar; Agra-Bermejo, Rosa; González-Salvado, Violeta; Iglesias-Alvarez, Diego; Bertomeu-Martínez, Vicente; González-Juanatey, Jose R.
Abstract: Introduction: Acute coronary syndrome (ACS) treatments increase bleeding complications that also impair prognosis. Bleeding risk scores reclassification of actual mortality risk estimated by the GRACE score might improve overall estimation. Methods: Observational and prospective study of all ACS patients admitted in two hospitals. Mortality risk was assessed by the GRACE score and bleeding risk by the CRUSADE score. We analyzed the net reclassification improvement (NRI) of adding the CRUSADE score to the GRACE score. Results: We included 6997 patients, mean age 67.4 (12.9), 38.0% ST-elevation ACS, mean GRACE score 145.2 (39.9). The percentage of patients with CRUSADE score > 20 or > 50 increased as the GRACE score was higher. Hospital mortality was 5.3% and the addition of the CRUSADE score reclassified a relevant percentage of patients with GRACE score > 109; NRI was 3.80% (1.10–6.10). During follow-up, (median 53.0 months) mortality rate was 22.6% and patients with CRUSADE score > 50 had significantly higher mortality rates in all GRACE score categories; NRI was high (46.6%, 95% CI 41.0–53.1). The multivariate analysis outlined the independent predictive value of CRUSADE score > 20 or > 50 as well as GRACE scores 109–139 and > 140. Conclusions: The addition of the CRUSADE score to the GRACE score improved mortality risk estimation. A CRUSADE score > 50 identified patients with higher post-discharge mortality and higher hospital mortality if GRACE score was > 109. The CRUSADE score improved hospital and long-term mortality prediction in patients with GRACE score > 140. Individual mortality risk estimation should integrate the CRUSADE and GRACE scores.